EFEKTIVITAS MODEL PEMBELAJARAN GI (GROUP INVESTIGATION) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI SMA NEGERI 1 ANGKOLA TIMUR - Indra Mahyana Harahap; Rahmatika Elindra (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2020)
The aim of this study is to describe the effectiveness of using GI learning model on students’ mathematical problem solving at the tenth grade students of SMA Negeri 1 Angkola Timur. The research was conducted by applying experimental method (one group pretest post test design) with 28 students and they were taken by using cluster sampling technique. Observation and test were used in collecting the data. Based on descriptive analysis, it was found: (a) the average of using GI learning model was 3.9 (very good category) and (b) the average of students’ mathematical problem solving before using GI learning model was 53.73 ( fair category) and after using GI learning model was 79.10 (good category). Furthermore, based on inferential statistic by using pair sample ttest, and help SPSS version 22, the result showed the significant value was less than 0.05 (0.000<0.05). It means, GI learning model was effective used on students’ mathematical problem solving at the tenth grade students of SMA Negeri 1 Angkola Timur.